Vegetative expression of the delta-endotoxin genes of Bacillus thuringiensis subsp. kurstaki in Bacillus subtilis. - Shivakumar, A G (1986)
Bacillus thuringiensis subsp. kurstaki total DNA was digested with BglII and cloned into the BamHI site of plasmid pUC9 in Escherichia coli. A recombinant plasmid, pHBHE, expressed a protein of 135,000 daltons that was toxic to caterpillars. A HincII-SmaI double digest of pHBHE was then ligated to BglII-cut plasmid pBD64 and introduced into Bacillus subtilis by transformation. The transformants were identified by colony hybridization and confirmed by Southern blot hybridization. A 135,000-dalton protein which bound to an antibody specific for the crystal protein of B. thuringiensis was detected from the B. subtilis clones containing the toxin gene insert in either orientation. A toxin gene insert cloned into a PvuII site distal from the two drug resistance genes of the pBD64 vector also expressed a 135,000-dalton protein. These results suggest that the toxin gene is transcribed from its own promoter. Western blotting of proteins expressed at various stages of growth revealed that the crystal protein expression in B. subtilis begins early in the vegetative phase, while in B. thuringiensis it is concomitant with the onset of sporulation. The cloned genes when transferred to a nonsporulating strain of B. subtilis also expressed a 135,000-dalton protein. These results suggest that toxin gene expression in B. subtilis is independent of sporulation. Another toxin gene encoding a 130,000- to 135,000-dalton protein was cloned in E. coli from a library of B. thuringiensis genes established in lambda 1059. This gene was then subcloned in B. subtilis. The cell extracts from both clones were toxic to caterpillars. Electron microscope studies revealed the presence of an irregular crystal inclusion in E. coli and a well-formed bipyramidal crystal in B. subtilis clones similar to the crystals found in B. thuringiensis.